Effectiveness of Short-term Intensive Dynamic Psychotherapy on the Severity of Gastrointestinal Symptoms and Depression in Patients with the Diarrhea Subtype of Irritable Bowel Syndrome - Hajrezaei, Mohammad Reza; Sazesh Rahbarjou, Seyedeh Sanaz; Shamsaldini, Ahmad (Journal of Assessment and Research in Applied Counseling (JARAC), 2024)
Objective: Irritable Bowel Syndrome (IBS) is one of the functional gastrointestinal disorders and the most common digestive disorder. The purpose of the current study was to investigate the effectiveness of short-term intensive dynamic psychotherapy on the severity of gastrointestinal symptoms and depression in patients with the diarrhea subtype and concurrent depression of Irritable Bowel Syndrome.Methods and Materials: The present study employed a single-case quasi-experimental design. Three patients with the diarrhea subtype and concurrent depression of Irritable Bowel Syndrome, who had visited neurology and psychiatry clinics in Qom in December 2023, were selected through purposive sampling and each received 18 sessions of short-term intensive dynamic psychotherapy. Data derived from the Somatic Symptom Scale by Solati Dekordi et al. (2009) and the Beck Depression Inventory-II (BDI-II) by Beck et al. (1996) were recorded at three stages (baseline, treatment, and follow-up) and analyzed using visual plotting methods, the Reliable Change Index, and the percentage of improvement formula.Findings: The percentage of improvement in the severity of gastrointestinal symptoms and the severity of depression symptoms for each patient in the treatment and follow-up stages was higher than 50%, indicating therapeutic success. The Reliable Change Index for the severity of gastrointestinal symptoms and depression severity for all three patients was above 1.96, indicating significant improvement.Conclusion: Short-term intensive dynamic psychotherapy appears to be effective in reducing the severity of gastrointestinal symptoms and depression in these patients. Therefore, it is recommended that randomized controlled trials with long-term follow-up be conducted as a continuation of this preliminary study.